2017
DOI: 10.18632/oncotarget.22161
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs and their role in cancer stem cells

Abstract: Cancer stem cells (CSCs) play a vital role in the formation of tumors and have been studied as a target of anticancer therapy. Long non-coding RNAs (lncRNAs) are important in the genesis and progression of cancer. Various lncRNAs, such as ROR, HOTAIR, H19, UCA1, and ARSR, are involved in cancer stemness. These lncRNAs could regulate the expression of CSC-related transcriptional factors, such as SOX2, OCT4, and NANOG, in colorectal, prostate, bladder, breast, liver, and other cancer types. In this work, we revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 72 publications
0
58
0
Order By: Relevance
“…Knocking down HOTAIR inhibits features of TICs including frequencies of side population cells and spheroid forming cells [88]. Chen and colleagues recently reviewed regulations of lncRNAs in TICs in several types of cancers [89]. Thus, it is imperative to find whether these lncRNAs are able to affect TICs involved in lung tumorigenesis to find avenues of targeting these lncRNAs.…”
Section: Role Of Non-coding Rnas In Lung Tumor Initiating Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Knocking down HOTAIR inhibits features of TICs including frequencies of side population cells and spheroid forming cells [88]. Chen and colleagues recently reviewed regulations of lncRNAs in TICs in several types of cancers [89]. Thus, it is imperative to find whether these lncRNAs are able to affect TICs involved in lung tumorigenesis to find avenues of targeting these lncRNAs.…”
Section: Role Of Non-coding Rnas In Lung Tumor Initiating Cellsmentioning
confidence: 99%
“…It is imperative that lncRNAs are studied to further our understanding of their mechanisms of action within lung cancer, especially since lncRNAs and miRNAs have been found to affect each other and lung cancer overall, as exemplified by RNA component of mitochondrial RNA processing endoribonuclease being able to affect miR-206 levels to activate oncogenes in lung cancer (see Table 2). As shown before, literature reviews such as "Long noncoding RNAs as regulators of cancer immunity" have summarized the role of non-coding RNAs in other types of cancers, and researchers can use this information to determine whether those non-coding RNAs are also able to affect lung cancer [89,163,185]. Furthermore, new and emerging technologies such as RNA editing and RNA modification warrant further research as they too have been implicated in altering lncRNAs and miRNAs to either promote or impede lung tumor initiation and progression.…”
Section: Concluding Remarks and Future Directionmentioning
confidence: 99%
“…Components of dysregulated CSC-enriched molecular pathways (e.g., Notch, Wnt, and Hh) may exemplify novel druggable targets for signaling antagonists [16,39,40]. Additionally, increasing evidence suggests that it may be possible to target CSCs via CSC-specific or associated non-coding RNAs [41][42][43][44].…”
mentioning
confidence: 99%
“…Recently, numerous studies revealed that various lncRNAs could regulate cancer stem cell (CSC) in numerous types of cancer via different molecular mechanisms, which involve differentiation, proliferation and self-renewal, promotion of the metastasis, invasion and prediction of prognosis, and targeted therapies. To date, ROR, HOTAIR, H19, UCA1, and ARSR are the most highlighted lncRNAs in CSCs [17]. Therefore, lncRNAs could be used as a new master regulators of resistance to systemic treatments in BC [18].…”
Section: Discussionmentioning
confidence: 99%